Enhancing Reading Comprehension by Using the Strategies of Scanning and Skimming for Institute of Technology Indonesia CIE's Fourth Level Students - Wiwik Yully Widyawati; Herlina Lindaria Simanjuntak (Scope : Journal of English Language Teaching, 2023)
The purpose of this research is to determine the students' of CIE fourth level achievement in reading skill by scanning and skimming strategies, as well as the effectiveness of scanning and skimming strategies at Institute of Technology Indonesia. The pre-experimental research technique was employed by using a one-group pretest-posttest design. The population of this research was a fourth level CIE class of 60 students, and the sample was a class of IV-A pupils of 20 students. The instrument was a 25-question of multiple-choice survey. The findings prior to utilizing the scanning and skimming method, pretest; the maximum score was 80, the lowest score was 56, the mean score was 70.6, the median score was 72; and the mode score was 72, the standard deviation was 8.13, and the variance was 66.15. The posttest findings of the scanning and skimming approach were as follows: the highest score was 100, the lowest score was 72, the mean score was 92, the median score was 96, the mode score was 96, the variance was 80.84, and the standard deviation was 8,99. Based on the findings of the research, the tcount was 4.352 with a significant threshold of 0.05 and the ttable was 2,086, and the scores were compared. As a result, tcount exceeds ttable (4.352 > 2,086).  It signifies that the research hypothesis (H1) has been accepted. In conclusion, utilizing scanning and skimming strategies has a considerable influence on reading comprehension at the fourth level students of Institute of Technology Indonesia.